Hubungan Psoriasis Dengan Komorbiditas Sistemik: Tinjauan Literatur - Wong, Hendra Wijaya; Kurniadi, Ivan; Yowen, Yowen (Jurnal MedScientiae, 2025)
Background: Psoriasis is a chronic inflammatory disease that not only affects the skin, but is also closely related to various systemic comorbidities. This literature review aims to examine the relationship between psoriasis and systemic comorbidities based on various recent studies. Methodology: Literature reviews made based on articles and journals are adjusted to the Inclusion and Exclusion Criteria. Journals were searched in medical databases through Pubmed, Google Scholar, Neliti, and Cochrane Library, using the keywords "psoriasis", "systemic comorbidity", "hypertension", "obesity", "diabetes mellitus", "coronary artery disease", "dyslipidemia" and "stroke". Results: From the 12 selected journals, it was found that systemic comorbidities such as hypertension, obesity, diabetes mellitus, coronary heart disease, dyslipidemia and stroke were related to psoriasis. Psoriasis patients have a higher risk of experiencing these comorbidities compared to the general population, especially in cases with moderate to severe severity. Conclusion: The results of the study indicate that psoriasis patients have a higher risk of experiencing comorbidities. Therefore, psoriasis should be viewed as a systemic disease that requires a multidisciplinary approach in management to reduce the risk of complications and improve the quality of life of patients. Further research is needed to develop effective prevention and treatment strategies for comorbidities in psoriasis patients. Keywords: psoriasis, systemic comorbidity, metabolic syndrome